Comparison of Plating Versus Intramedullary Nailing in Metaphyseal Fractures: A Systematic Review and Meta-Analysis - Anak Agung Ngurah Bagus Surya Darma; I Wayan Subawa (Indonesian Journal of Global Health Research, 2025)
Metaphyseal fractures are common orthopedic injuries that often require surgical intervention for optimal management. The choice between plating and intramedullary nailing as fixation methods remains a subject of debate among orthopedic surgeons, with considerations including fracture type, patient characteristics, and surgical outcomes. This study aim to compare the efficacy, safety, and outcomes of plating versus intramedullary nailing in the treatment of metaphyseal fractures.Methods: A comprehensive search was conducted across major electronic databases for relevant studies published up to 2023. Studies comparing plating and nailing techniques in metaphyseal fracture fixation were included. Data regarding study characteristics, patient demographics, surgical techniques, outcomes, and follow-up durations were extracted and analyzed using appropriate statistical methods. Our primary outcomes were union rate and time, functional outcome using patient reported outcome measure, and complications. Results: The initial search yielded a total of 687 studies, of which 7 studies met the inclusion criteria, consisting of a total of 758 skeletally-mature patients with metaphyseal fractures treated with either intramedullary nailing or plate fixations. The meta-analysis revealed that there is no evidence to draw definitive conclusions on which indicates the best method in treating metaphyseal fractures. Subgroup analyses were performed based on fracture type, patient age, and other relevant factors to further elucidate the comparative effectiveness of plating versus screwing.Conclusion: The meta-analysis findings indicated that using intramedullary nailing led to shorter surgical and complications when compared to plate fixation. Additionally, both treatments frequently resulted in similar union times and union-related issues. However, further randomized controlled trials (RCTs) are necessary to bolster the existing evidence base.